Zirconia sintered body and method for manufacturing the same

A zirconia sintered body with a tailored particle size distribution and stabilizer achieves high light transmittance and strength, addressing the limitations of existing dental materials for anterior teeth and canines.

KR103041351B1Active Publication Date: 2026-10-30KURARAY NORITAKE DENTAL
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
KR1020247021928
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-27
Filing Date
2022-12-26
Publication Date
2026-10-30
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

Existing zirconia sintered bodies used in dental applications lack sufficient light transmittance and strength, particularly for anterior teeth and canines like central incisors and lateral central incisors, necessitating further improvements in both properties.

Method used

A zirconia sintered body with a specific particle size distribution, including 20 to 50% of particles with a size of 0.45 μm or more and less than 1 μm, and a stabilizer like yttria, combined with a balanced ratio of tetragonal and cubic crystal systems, to enhance light transmittance and strength.

Benefits of technology

The zirconia sintered body achieves high light transmittance and strength, suitable for dental applications, with a biaxial bending strength of 550 MPa or more and translucency comparable to natural teeth, while maintaining aesthetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112024070887932-PCT00003_ABST
    Figure 112024070887932-PCT00003_ABST
Patent Text Reader

Abstract

The present invention provides a zirconia sintered body that combines high light transmittance and high strength, which can be preferably used in anterior teeth and canines (particularly central incisors and lateral central incisors), and a method for manufacturing the same. The present invention relates to a zirconia sintered body comprising zirconia and a stabilizer capable of suppressing the phase transition of zirconia, wherein the crystal grains of the zirconia sintered body contain, in a particle size distribution based on the number of particles, particles with a particle size of 0.45 μm or more and less than 1 μm in a ratio of 20 to 50%, and said particle size is a diameter that passes through the center of gravity of the particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a zirconia sintered body and a method for manufacturing the same. More specifically, the present invention relates to a zirconia sintered body that combines high light transmittance and high strength, which can be preferably used in anterior teeth and canines (particularly central incisors and lateral central incisors), and a method for manufacturing the same. Background Technology

[0002] Sintering of ceramics is generally a mass transfer phenomenon in which the free energy of the system decreases. When ceramic powder is solid-state sintered, the primary particles contained in the powder grow with decreasing surface area and interfaces over time, depending on their particle size and sintering temperature. It is known that particle growth is more likely to occur when the particle size contained in the powder is small and the difference between the particle size of the mass transfer site and the particle size is large.

[0003] Furthermore, it is generally known that in sintered ceramic bodies, the grain boundary area increases and the higher the strength and toughness tend to be as the particle size contained within the sintered body decreases. Additionally, it is known that in sintered ceramic bodies, the more particles with a particle size sufficiently larger than the wavelength of visible light are contained, the more light scattering by the particles is suppressed and the light transmittance of the sintered body tends to increase. Therefore, for the simultaneous achievement of strength and light transmittance in ceramics, it is required that the sintered body contain both small particle sizes and sufficiently large particles.

[0004] As a ceramic, for example, zirconia has high strength and also high toughness, so a zirconia sintered body (hereinafter referred to as a "partially stabilized zirconia sintered body") in which a small amount of yttria (yttrium oxide; Y2O3) is dissolved as a stabilizer is used.

[0005] When using partially stabilized zirconia sintered bodies as dental materials, optical properties such as translucency and hue are required not only in terms of mechanical properties like high strength and high toughness, but also in terms of aesthetics specific to dental applications. To date, regarding partially stabilized zirconia sintered bodies, research has been conducted on zirconia sintered bodies that possess high strength and toughness, as well as aesthetics intended to mimic natural teeth.

[0006] For example, Patent Documents 1 and 2 can be cited. In Patent Document 1, a cross-sectional photograph of a zirconia sintered body is shown, in which the cross-sectional area of ​​each zirconia particle is calculated, and from the cross-sectional area, the equivalent particle size of each zirconia particle is calculated assuming that each zirconia particle is circular, and the zirconia particle size is classified into three classes: less than 0.4 μm, 0.4 μm or more and less than 0.76 μm, and 0.76 μm or more. A zirconia sintered body is disclosed in which the cross-sectional area ratio of zirconia particles with an equivalent particle size of less than 0.4 μm is 4% or more and 35% or less, the cross-sectional area ratio of zirconia particles with an equivalent particle size of 0.4 μm or more and less than 0.76 μm is 24% or more and 57% or less, and the cross-sectional area ratio of zirconia particles with an equivalent particle size of 0.76 μm or more is 16% or more and 62% or less. In addition, the zirconia sintered body is disclosed to have high bending strength and fracture toughness and to have appropriate transparency, and in Example 1, the transmittance is disclosed to be 30%.

[0007] In addition, Patent Document 2 discloses a transparent zirconia sintered body containing yttria of more than 4.0 mol% and less than 6.5 mol% and alumina of less than 0.1 wt%, having a relative density of 99.82% or more, a total light transmittance of 37% or more and less than 40% for light of a wavelength of 600 nm at a thickness of 1.0 mm, and a bending strength of 500 MPa or more. Prior art literature

[0008] International Publication No. 2014 / 142080, Japanese Patent Publication No. 2015-143178 The problem to be solved

[0009] As confirmed by the inventors, the zirconia sintered body of Patent Document 1 has a suitable transparency, but the light transmittance required for anterior teeth and canines (especially central incisors and lateral central incisors) is gradually increasing, and since higher light transmittance (e.g., the transmittance required for central incisors, etc. is about 40% or more) is required, there was room for further improvement regarding the light transmittance of the zirconia sintered body in order to manufacture a dental product for anterior teeth and canines that satisfies such requirements.

[0010] In addition, as confirmed by the inventors, the zirconia sintered body of Patent Document 2 had low biaxial bending strength, so there was room for further improvement regarding strength.

[0011] The present invention aims to provide a zirconia sintered body that combines high light transmittance and high strength, which can be preferably used in anterior teeth and canines (particularly central incisors and lateral incisors), and a method for manufacturing the same. means of solving the problem

[0012] The inventors, as a result of repeated diligent research to solve the above problem, discovered that high light transmittance and high strength can be achieved by including 20 to 50 percent of particles with a particle size of 0.45 μm or more and less than 1 μm in the crystal grains of a zirconia sintered body in the particle size distribution based on the number of particles. Based on this finding, they conducted further research and came to complete the present invention.

[0013] That is, the present invention includes the following inventions.

[0014] [1] A zirconia sintered body comprising zirconia and a stabilizer capable of suppressing the phase transition of zirconia,

[0015] The crystal grains of the above zirconia sintered body contain, in a particle size distribution based on the number of particles, particles with a particle size of 0.45 μm or more and less than 1 μm in a ratio of 20 to 50%,

[0016] A zirconia sintered body in which the above particle diameter is the diameter passing through the center of gravity of the particle.

[0017] [2] The zirconia sintered body described in [1] contains, in a particle size distribution based on the number of particles, particles with a particle size of less than 0.45 μm in a ratio of 20 to 70 percent.

[0018] [3] A zirconia sintered body described in [1] or [2], wherein the crystal particles of the zirconia sintered body contain 6 to 35% of particles with a particle size of 1 μm or more in the particle size distribution based on the number of particles.

[0019] [4] A zirconia sintered body described in any one of [1] to [3], wherein the ratio of the tetragonal system to the sum of the tetragonal system and the cubic system, calculated by the following formula (1), is 0 to 70%.

[0020] f t / (t+c) = 100 × I t / ( I t + I c ) (1)

[0021] (in the food, f t / (t+c) represents the ratio of tetragonal to (tetragonal + cubic) in the zirconia sintered body measured by X-ray diffraction, and I t represents the height of the peak near 2θ = 30.2° (peak based on the tetragonal system), and I c represents the height of the peak near 2θ = 30.1° (the peak based on the cubic system).

[0022] [5] A zirconia sintered body described in [4], in which the ratio of the tetragonal system to the sum of the tetragonal and cubic systems is 40 to 65 percent.

[0023] [6] A zirconia sintered body described in any one of [1] to [5], having a biaxial bending strength of 550 MPa or more as measured in accordance with JIS T 6526 : 2012.

[0024] [7] The above-mentioned stabilizer is yttria, [1] to [6] a zirconia sintered body.

[0025] [8] A zirconia sintered body described in [7], having a yttria content of 3.0 to 7.5 mol% relative to the total mol of zirconia and yttria.

[0026] [9] A method for manufacturing a zirconia sintered body comprising zirconia and a stabilizer capable of suppressing the phase transition of zirconia,

[0027] Using a raw material powder comprising zirconia powder and a stabilizer powder capable of suppressing the phase transition of zirconia,

[0028] A method for manufacturing a zirconia sintered body as described in any one of [1] to [8], wherein the above-mentioned stabilizer powder has at least one peak top in the range of particle size 0.05 to 0.40 μm in the volume-based particle size distribution, and also has at least one peak top in the range of particle size 0.5 μm or more.

[0029]

[10] A method for manufacturing a zirconia sintered body as described in [9], wherein the ratio (A) : (B) of the frequency of peak tops in the range of particle size 0.05 to 0.40 μm and the frequency of peak tops in the range of particle size 0.5 μm or more (B) in the volume-based particle size distribution of the above stabilizer powder is 40 : 60 to 85 : 15.

[0030]

[11] The above-mentioned stabilizer is yttria, [9] or

[10] a method for manufacturing a zirconia sintered body.

[0031]

[12] A method for manufacturing a zirconia sintered body as described in

[11] , wherein the yttria content is 3.0 to 7.5 mol% relative to the total mol of zirconia and yttria.

[0032]

[13] A method for manufacturing a zirconia sintered body as described in any one of [9] to

[12] , by molding the above raw material powder to manufacture a zirconia molded body.

[0033]

[14] A method for manufacturing a zirconia sintered body as described in

[13] , by plasticizing the above zirconia molded body to produce a zirconia plastic body.

[0034]

[15] A method for manufacturing a zirconia sintered body as described in

[13] or

[14] , by firing the zirconia molded body or the zirconia plastic body described above.

[0035]

[16] A method for manufacturing a zirconia plastic comprising zirconia and a stabilizer capable of inhibiting the phase transition of zirconia,

[0036] Using a raw material powder comprising zirconia powder and a stabilizer powder capable of suppressing the phase transition of zirconia,

[0037] A method for manufacturing a zirconia plastic, wherein the above-mentioned stabilizer powder comprises a powder having at least one peak top in a range of particle size of 0.05 to 0.40 μm and at least one peak top in a range of particle size of 0.5 μm or more in a volume-based particle size distribution.

[0038]

[17] A method for manufacturing a zirconia plastic described in

[16] , by molding the above raw material powder to produce a zirconia molded body.

[0039]

[18] A method for manufacturing a zirconia plastic described in

[17] , which plasticizes the above zirconia molded body.

[0040]

[19] A method for preparing a zirconia-containing composition comprising zirconia and a stabilizer capable of inhibiting the phase transition of zirconia,

[0041] The above zirconia raw material is crushed to produce zirconia powder, and

[0042] The raw material of the above-mentioned stabilizer is ground to produce stabilizer powder, and

[0043] A zirconia composition, which is a raw material powder, is prepared by mixing the above zirconia powder and the above stabilizer powder, and

[0044] A method for preparing a zirconia-containing composition, wherein the above-mentioned stabilizer powder comprises a powder having at least one peak top in a range of particle size of 0.05 to 0.40 μm and at least one peak top in a range of particle size of 0.5 μm or more in a volume-based particle size distribution.

[0045]

[20] A method for preparing a zirconia-containing composition as described in

[19] , wherein the grinding time of the raw material of the above-mentioned stabilizer is 30 hours or less.

[0046]

[21] A method for preparing a zirconia-containing composition as described in

[19] or

[20] , wherein the grinding time of the raw material of the zirconia above is 20 hours or more.

[0047]

[22] A method for preparing a zirconia-containing composition in which the above-mentioned stabilizer is yttria,

[19] to

[21] . Effects of the invention

[0048] According to the present invention, a zirconia sintered body having both high light transmittance and high strength, which can be preferably used in anterior teeth and canines (particularly central incisors and lateral central incisors), and a method for manufacturing the same can be provided. Furthermore, according to the manufacturing method of the present invention, a zirconia sintered body having both high light transmittance and high strength can be provided even when fired in a short time. Brief explanation of the drawing

[0049] Figure 1 shows the particle size distribution (based on volume) of the yttria powder used in the raw material powders of Examples 1 to 14. Figure 2 shows an electron microscope image of a zirconia sintered body related to Example 5. Figure 3 shows an electron microscope image of a zirconia sintered body related to Comparative Example 1. Figure 4 shows an electron microscope image of a zirconia sintered body related to Comparative Example 4. Specific details for implementing the invention

[0050] A zirconia sintered body comprising the zirconia of the present invention and a stabilizer capable of suppressing the phase transition of the zirconia, wherein the crystal grains of the zirconia sintered body contain, in a particle size distribution based on the number of particles, particles with a particle size of 0.45 μm or more and less than 1 μm in a ratio of 20 to 50%. Furthermore, the particle size refers to the diameter passing through the center of gravity of the particles. The method for measuring the particle size distribution based on the number of particles is as described in the examples described below. The measurement site is not particularly limited and may be the surface of the zirconia sintered body or the cross-section of the zirconia sintered body.

[0051] In addition, in this specification, the upper and lower limits of the numerical range (content of each component, value calculated from each component, and each physical property, etc.) can be appropriately combined.

[0052] In the present invention, the particle size distribution is based on the number of particles. For example, in Patent Document 1, as shown in Table 2, the particle size distribution is examined based on the area, which calculates the total area and selects the ratio of the area. However, according to the inventors' investigation, it was discovered that when examined based on the number of particles, particles with a particle size of 0.45 μm or more and less than 1 μm (hereinafter also referred to as "heavy particles") act in a direction that reduces light transmittance and strength depending on the ratio, in relation to the influence of the stabilizer. Since Patent Document 1 calculates based on the area ratio, the area ratio changes significantly with only one increase in large particles. On the other hand, since the present invention evaluates the number ratio of particles, the light transmittance and strength resulting from the abundance ratio of particles of each size can be increased more efficiently.

[0053] In the zirconia sintered body of the present invention, the crystal grains include particles with a particle size of 0.45 μm or more and less than 1 μm in a ratio of 20 to 50% in the particle size distribution based on the number. By setting the ratio of heavy particles to a predetermined ratio in the particle size distribution based on the number, the light transmittance mainly caused by particles with a particle size of 1 μm or more can be further increased, and the strength mainly caused by particles with a particle size of less than 0.45 μm can be increased.

[0054] The proportion of heavy particles is preferably 21% or more in terms of the transparency and strength of the zirconia sintered body, more preferably 22% or more, even more preferably 23% or more, and particularly preferably 24% or more. In addition, the proportion of heavy particles is preferably 49% or less in terms of the transparency and strength of the zirconia sintered body, more preferably 40% or less, even more preferably 36% or less, and particularly preferably 30% or less. The preferred range of the proportion of heavy particles can be appropriately combined from the upper and lower limits above, for example, it may be 21% to 49%, 22% to 40%, or 23% to 36%.

[0055] If the proportion of heavy particles exceeds 50% in the particle size distribution, it is undesirable because the strength and light transmittance of the zirconia sintered body decrease. Also, if the proportion of heavy particles is less than 20% in the particle size distribution, it is undesirable because the difference in refractive index between particles with a particle size of less than 0.45 μm (hereinafter also referred to as "small particles") and particles with a particle size of 1 μm or more (hereinafter also referred to as "large particles") increases, causing light scattering and potentially significantly reducing the overall light transmittance. By having heavy particles in a predetermined ratio, the difference in refractive index is buffered, and light scattering is suppressed when light passes from small particles to large particles.

[0056] In addition, in the zirconia sintered body of the present invention, it is preferable that the crystal grains include particles with a particle size of less than 0.45 μm in a ratio of 20 to 70 percent in the particle size distribution based on the number. In terms of further improving the strength of the zirconia sintered body, it is more preferable that the ratio of small particles be 22 percent or more, even more preferable that it be 30 percent or more, and particularly preferable that it be 35 percent or more. In addition, in terms of further improving the strength of the zirconia sintered body, it is more preferable that the ratio of small particles be 69 percent or less, even more preferable that it be 68.5 percent or less, and particularly preferable that it be 68 percent or less.

[0057] In addition, in the zirconia sintered body of the present invention, it is preferable that the crystal grains include particles with a particle size of 1 μm or more in a ratio of 6 to 35% in the particle size distribution based on the number. In terms of further improving the light transmittance of the zirconia sintered body, it is more preferable that the ratio of large particles be 6.5% or more, even more preferable that it be 7% or more, and particularly preferable that it be 8% or more. In addition, in terms of further improving the light transmittance of the zirconia sintered body, it is more preferable that the ratio of large particles be 33% or less, even more preferable that it be 30% or less, and particularly preferable that it be 20% or less.

[0058] In addition, in the zirconia sintered body of the present invention, the mixing balance of each particle may be adjusted in addition to the ratios of the medium, small, and large particles to ensure superior transparency and strength. In the zirconia sintered body of the present invention, in terms of particle size distribution (%) based on number, it is preferable that the proportion of small particles is the highest among the three particles, and it is more preferable that the proportion of small particles is 1.5 times or more the proportion of medium particles. In addition, in terms of the zirconia sintered body of the present invention, in terms of superior transparency and strength, it is preferable that the proportion of large particles is the lowest, and it is more preferable that the proportion of large particles is 0.8 times or less the proportion of medium particles.

[0059] The main crystal system of the zirconia sintered body of the present invention may be either a tetragonal or a cubic system, but in terms of the transparency and strength of the zirconia sintered body, it is preferable that the tetragonal and cubic systems are mixed in a certain ratio. The main crystal system refers to the crystal system that has the highest proportion compared to other crystal systems with respect to the total amount of all crystal systems (monoclinic, tetragonal, and cubic systems) in zirconia.

[0060] In the zirconia sintered body, it is preferable that the ratio of tetragonal to (tetragonal + cubic) (hereinafter also referred to as "ratio of tetragonal to the sum of tetragonal and cubic systems") is less than 80%, and it is more preferable that it is 70% or less, 65% or less, and particularly preferable that it is 50% or less, as the transparency and strength of the zirconia sintered body are superior. In addition, it is preferable that it is 0% or more, and it is more preferable that it is 30% or more, as the strength of the zirconia sintered body is superior, and it is more preferable that it is 40% or more, and particularly preferable that it is 41% or more, as the transparency and strength of the zirconia sintered body are superior. The preferred range of the ratio of the tetragonal system to the sum of the tetragonal system and the cubic system can be appropriately combined from the upper and lower limits mentioned above, for example, it may be 40% or more and 65% or less, or 41% or more and 50% or less.

[0061] In the zirconia sintered body of the present invention, the ratio of the tetragonal system to the sum of the tetragonal system and the cubic system in the crystal system of the zirconia is calculated by the following formula (1).

[0062] f t / (t+c) = 100 × I t / ( I t + I c ) (1)

[0063] (in the food, f t / (t+c) represents the ratio of tetragonal to (tetragonal + cubic) in the zirconia sintered body measured by X-ray diffraction, and I t represents the height of the peak near 2θ = 30.2° (peak based on the tetragonal system), and I c represents the height of the peak near 2θ = 30.1° (the peak based on the cubic system).

[0064] The ratio of the tetragonal system to the sum of the tetragonal and cubic systems can be calculated using Equation (1) by performing X-ray diffraction (XRD) measurements and using the measurement results.

[0065] The biaxial bending strength of the zirconia sintered body of the present invention is preferably 550 MPa or higher, more preferably 600 MPa or higher, even more preferably 650 MPa or higher, and particularly preferably 700 MPa or higher. The biaxial bending strength can be measured in accordance with JIS T 6526:2012. Specifically, it can be measured by the method described in the examples described below.

[0066] Transparency (ΔL) of the zirconia sintered body of the present invention * (WB)) is preferably 13 or higher in terms of manufacturing a prosthesis having a color tone closer to that of natural teeth, particularly incisors and canines (e.g., central incisors, lateral incisors), is more preferably 14 or higher in terms of making it easier to manufacture a prosthesis having a color tone closer to that of incisors, and is even more preferably 15 or higher.

[0067] Translucency (ΔL * (WB) is the lightness (L) when chromaticity is measured against a white background using a spectrophotometer manufactured by Olympus Corporation (product name "CrystalEye"), measurement mode: 7-band LED light source. W * ) and the lightness (L) when chromaticity is measured on a black background using the same sample, the same measuring device, measurement mode, and light source. B * ) measures, and the difference between the two (ΔL * = (L W * ) - (L B * It is calculated as )). Measurement conditions, such as the size of the test specimen, are as described in the examples described later.

[0068] A stabilizer capable of suppressing the phase transition of zirconia (hereinafter also simply referred to as a "stabilizer") is preferably capable of forming partially stabilized zirconia. Examples of such stabilizers include calcium oxide (CaO), magnesium oxide (MgO), yttria (yttrium oxide; Y2O3), cerium oxide (CeO2), scandium oxide (Sc2O3), niobium oxide (Nb2O5), lanthanum oxide (La2O3), erbium oxide (Er2O3), and praseodymium oxide (Pr6O2). 11 Examples of oxides include , Pr2O3), samarium oxide (Sm2O3), europium oxide (Eu2O3), and thulium oxide (Tm2O3), and yttria is preferred. The stabilizer may be used alone or in combination of two or more types.

[0069] The content of the stabilizer in the zirconia sintered body of the present invention can be measured, for example, by inductively coupled plasma (ICP) emission spectroscopy, fluorescence X-ray analysis, etc.

[0070] In the zirconia sintered body of the present invention, the content of the stabilizer is preferably 0.1 to 18 mol% with respect to the total mol of zirconia and the stabilizer, more preferably 1 to 15 mol%, and even more preferably 1.5 to 10 mol%.

[0071] In the zirconia sintered body of the present invention, when the stabilizer is yttria, the content of yttria is preferably 3.0 mol% or more with respect to the total mol of zirconia and yttria, in terms of the light transmittance and strength of the zirconia sintered body, more preferably 4.5 mol% or more, and even more preferably 5.0 mol% or more in terms of the light transmittance and strength of the zirconia sintered body.

[0072] In addition, regarding the light transmittance and strength of the zirconia sintered body, the yttria content is preferably 7.5 mol% or less with respect to the total mol of zirconia and yttria, more preferably 7.0 mol% or less, and even more preferably 6.5 mol% or less. The preferred range of the yttria content can be appropriately combined from the upper and lower limit ranges mentioned above, for example, it may be 3.0 mol% or more and 7.5 mol% or less, or 4.5 mol% or more and 6.5 mol% or less. In one embodiment, the yttria content may be 4.0 mol% or more.

[0073] In addition, another embodiment of the present invention may include a method for manufacturing a zirconia sintered body, wherein a raw material powder comprising zirconia powder and a stabilizer powder capable of suppressing the phase transition of zirconia is used, and the stabilizer powder comprises a powder having at least one peak top in a range of 0.05 to 0.40 μm in a volume-based particle size distribution and at least one peak top in a range of 0.5 μm or more.

[0074] The volume-based particle size distribution can be measured by using, for example, a laser diffraction / scattering particle size distribution measuring device manufactured by Horiba Corporation (product name "Partica LA-950"), ultrasonically irradiating a slurry diluted with water for 30 minutes, and then measuring it on a volume basis while applying ultrasound.

[0075] Regarding the stabilizer capable of suppressing the phase transition of zirconia in the method for manufacturing a zirconia sintered body, the type and content are the same as those described in the zirconia sintered body.

[0076] In the zirconia sintered body after firing, in order to obtain the desired ratio of medium, large, and small particles as described above, the stabilizer powder comprises a powder having at least one peak top in the range of particle size of 0.05 to 0.40 μm and at least one peak top in the range of particle size of 0.5 μm or more in the volume-based particle size distribution. For example, a particle size distribution such as the result of the example described later (Fig. 1) is preferred.

[0077] In one preferred embodiment, a method for manufacturing a zirconia sintered body can be cited, wherein raw material powder comprising zirconia powder and a stabilizer powder capable of suppressing phase transition of zirconia is used in the zirconia sintered body after firing, in order to easily obtain the desired ratio of medium, large, and small particles as described above, and wherein the stabilizer powder comprises a powder having one peak top in the range of particle size of 0.05 to 0.40 μm and one peak top in the range of particle size of 0.5 μm or more in the particle size distribution based on volume.

[0078] In the particle size distribution of the above-mentioned stabilizer powder, the ratio (A) : (B) of the frequency of peak tops in the range of particle size 0.05 to 0.40 μm and the frequency of peak tops in the range of particle size 0.5 μm or larger is preferably 40 : 60 to 85 : 15, more preferably 45 : 55 to 82 : 18, and even more preferably 50 : 50 to 80 : 20, in order to obtain the desired ratio of medium, large, and small particles. The above ratio (A) : (B) is calculated from the following two formulas.

[0079] Ratio (A) = Frequency of peak tops (A) / (Frequency of peak tops (A) + Frequency of peak tops (B)) × 100

[0080] Ratio (B) = Frequency of peak tops (B) / (Frequency of peak tops (A) + Frequency of peak tops (B)) × 100

[0081] (In the formula, the frequency of peak tops (A) represents the frequency (%) of peak tops in the range of particle diameters 0.05 to 0.40 μm, and the frequency of peak tops (B) represents the frequency (%) of peak tops in the range of particle diameters 0.5 μm or larger.)

[0082] The frequency of peak tops (A) and the frequency of peak tops (B) can be identified as the height of the peaks, for example, in Fig. 1.

[0083] In addition, in any of the above embodiments, the range of particle size may be 0.1 to 0.40 μm. For example, another preferred embodiment may be a method for manufacturing a zirconia sintered body, wherein a raw material powder comprising zirconia powder and a stabilizer powder capable of suppressing the phase transition of zirconia is used, and the stabilizer powder comprises a powder having at least one peak top in the range of particle size of 0.1 to 0.40 μm and at least one peak top in the range of particle size of 0.5 μm or more in the volume-based particle size distribution.

[0084] In addition, the method for manufacturing the above-mentioned zirconia sintered body preferably includes a process of manufacturing a zirconia molded body by molding raw material powder. The molding method is not particularly limited, and can be molded into a desired shape (block shape, disc shape, etc.) using a known method (e.g., press molding).

[0085] For the zirconia molded body, from the perspective of handling, it is preferable that the biaxial bending strength be within the range of 2 to 10 MPa, and more preferable that it be within the range of 5 to 8 MPa. In addition, the biaxial bending strength of the zirconia molded body can be measured in accordance with JIS T 6526:2012.

[0086] In addition, the method for manufacturing the zirconia sintered body preferably includes a process of manufacturing a zirconia plastic by plasticizing a zirconia molded body.

[0087] In this specification, a zirconia plastic is a semi-sintered body in which zirconia particles (powder) are necked (fixed) and formed into a block without being completely sintered.

[0088] The density of the zirconia plastic of the present invention is preferably 2.75 g / cm³ or higher, more preferably 2.85 g / cm³ or higher, and even more preferably 2.95 g / cm³ or higher, in terms of increasing the transparency and strength of the zirconia sintered body.

[0089] The bending strength of the zirconia plastic of the present invention is preferably 15 MPa or higher to ensure strength that enables machining. In addition, the bending strength of the plastic is preferably 70 MPa or lower to facilitate machining, and more preferably 60 MPa or lower.

[0090] The above bending strength can be measured in accordance with ISO 6872:2015 (Dentistry - Ceramic materials), but the measurement is performed using a specimen of size 5 mm × 10 mm × 50 mm by changing only the condition of the specimen size. The face and C-face (the surface where the corner of the specimen is chamfered at a 45° angle) of the specimen are finished longitudinally with 600-grit sandpaper. The specimen is positioned so that its widest face faces the vertical direction (load direction). In the 3-point bending test measurement, the distance between supports (span) is 30 mm, and the crosshead speed is 0.5 mm / min.

[0091] The zirconia plastic of the present invention may contain additives other than zirconia and stabilizers, provided that the effects of the present invention are exhibited. Examples of such additives include coloring agents (including pigments, complex pigments, and fluorescent agents), binders, dispersants, defoaming agents, plasticizers, alumina (Al2O3), titanium oxide (TiO2), silica (SiO2), etc. One type of additive may be used alone, or two or more types may be used in combination.

[0092] Examples of pigments include oxides of at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr2O3, etc.).

[0093] Examples of composite pigments include composite oxides such as (Zr,V)O2, Fe(Fe,Cr)2O4, (Ni,Co,Fe)(Fe,Cr)2O4·ZrSiO4, and (Co,Zn)Al2O4.

[0094] As fluorescent agents, for example, Y2SiO5: Ce, Y2SiO5: Tb, (Y,Gd,Eu)BO3, Y2O3: Eu, YAG: Ce, ZnGa2O4: Zn, BaMgAl 10 O 17 Examples include Eu, etc.

[0095] Examples of binders include organic binders. Examples of organic binders include acrylic binders, paraffin binders, fatty acid binders, polyvinyl alcohol binders, etc.

[0096] Examples of dispersants include, for instance, ammonium polycarboxylate (triammonium citrate, etc.), ammonium polyacrylate, acrylic copolymer resin, acrylic acid ester copolymer, polyacrylic acid, bentonite, carboxymethylcellulose, anionic surfactants (for example, polyoxyethylene alkyl ether phosphate esters such as polyoxyethylene lauryl ether phosphate ester), nonionic surfactants, olein glycerides, amine salt type surfactants, oligosaccharide alcohols, stearic acid, etc.

[0097] Examples of antifoaming agents include alcohol, polyether, silicone, wax, etc.

[0098] Examples of plasticizers include polyethylene glycol, glycerin, propylene glycol, dibutylphthalic acid, etc.

[0099] To ensure block formation, the calcination temperature is preferably, for example, 800°C or higher, more preferably 900°C or higher, and even more preferably 950°C or higher. Additionally, to improve dimensional accuracy, the calcination temperature is preferably, for example, 1200°C or lower, more preferably 1150°C or lower, and even more preferably 1100°C or lower. For the method of manufacturing the zirconia plastic, the temperature is preferably 800°C to 1200°C. At such calcination temperatures, it is believed that solid solution of the stabilizer does not proceed. There are no particular limitations on the calcination, and a known calcination furnace may be used.

[0100] The zirconia plastic of the present invention can be manufactured into a machined body by machining. The machining method is not limited to a specific method, and an appropriately preferred method can be selected depending on the purpose. For example, if the zirconia plastic is in the shape of a disc, the disc can be machined into the shape of a dental product (e.g., a crown-shaped prosthesis) using a CAD / CAM system to manufacture a machined body. Examples of dental products include copings, frameworks, crowns, crown bridges, abutments, implants, implant screws, implant fixtures, implant bridges, implant burs, brackets, denture bases, inlays, onlays, orthodontic wires, laminate veneers, etc.

[0101] In addition, the method for manufacturing the zirconia sintered body preferably includes a process of firing a zirconia molded body or a zirconia plastic. The zirconia sintered body can be manufactured by firing a zirconia molded body or a zirconia plastic at a temperature at which zirconia particles reach sintering (sintering process).

[0102] The firing temperature (maximum firing temperature) can be appropriately changed depending on the composition of the zirconia molded body or the zirconia plastic body, and is not particularly limited, but 1350°C or higher is preferred, 1450°C or higher is more preferred, and 1500°C or higher is even more preferred. The upper limit of the firing temperature is not particularly limited, but, for example, 1700°C or lower is preferred, 1650°C or lower is more preferred, and 1600°C or lower is even more preferred. For firing, a known firing furnace may be used without particular limitation.

[0103] In the sintering process, the holding time at the sinterable temperature (maximum firing temperature) is preferably 120 minutes or less, more preferably 90 minutes or less, even more preferably 75 minutes or less, even more preferably 60 minutes or less, particularly preferably 45 minutes or less, and most preferably 30 minutes or less. Additionally, the holding time may be 25 minutes or less, 20 minutes or less, or 15 minutes or less when firing for a shorter time. Furthermore, the holding time is preferably 1 minute or more, more preferably 5 minutes or more, and even more preferably 10 minutes or more. According to the present invention, even with such a short firing time, the decrease in light transmittance of the manufactured zirconia sintered body can be suppressed and high strength can be maintained. In addition, by shortening the firing time, production efficiency can be increased and energy costs can be reduced.

[0104] In the sintering process, the heating rate and the heating rate are preferably set to shorten the time required for the sintering process and are not particularly limited.

[0105] In addition, another embodiment of the present invention may be a method for manufacturing a zirconia plastic comprising zirconia and a stabilizer capable of suppressing the phase transition of zirconia, wherein a raw material powder comprising zirconia powder and a stabilizer powder capable of suppressing the phase transition of zirconia is used, and the stabilizer powder comprises a powder having at least one peak top in a range of 0.05 to 0.40 μm in a volume-based particle size distribution and at least one peak top in a range of 0.5 μm or more.

[0106] In the method for manufacturing a zirconia plastic, the stabilizer capable of suppressing the phase transition of zirconia is the same as the type and content described in the zirconia sintered body. Also, regarding the ratio (A) : (B) of the frequency of peak tops in the range of particle size 0.05 to 0.40 μm and the frequency of peak tops in the range of particle size 0.5 μm or more of the stabilizer powder, the ratio is the same as that in the method for manufacturing a zirconia sintered body.

[0107] In addition, the method for manufacturing the above-mentioned zirconia plastic body preferably includes a process of manufacturing a zirconia molded body by molding raw material powder. The molding method is not particularly limited, and can be molded into a desired shape (block shape, disc shape, etc.) using a known method (e.g., press molding).

[0108] In addition, the method for manufacturing the zirconia plastic body preferably includes a process of manufacturing the zirconia plastic body by plasticizing a zirconia molded body.

[0109] Regarding the plasticization in the method for manufacturing a zirconia plastic, the plasticization temperature and furnace are the same as those in the method for manufacturing a zirconia sintered body.

[0110] In addition, another embodiment of the present invention may be a method for preparing a zirconia-containing composition comprising zirconia and a stabilizer capable of suppressing the phase transition of zirconia, wherein the raw material of the zirconia is crushed to produce zirconia powder, the raw material of the stabilizer is crushed to produce a stabilizer powder, and the zirconia powder and the stabilizer powder are mixed to produce a zirconia composition which is a raw material powder, wherein the stabilizer powder comprises a powder having at least one peak top in the range of a particle size of 0.05 to 0.40 μm and at least one peak top in the range of a particle size of 0.5 μm or more in the particle size distribution based on volume.

[0111] Regarding the stabilizer capable of suppressing the phase transition of zirconia in the method for manufacturing a zirconia-containing composition, the type and content are the same as those described in the zirconia sintered body.

[0112] The case where the stabilizer is yttria is explained below as an example.

[0113] The yttria raw material is ground using a known method (e.g., a ball mill), and the grinding time of the yttria raw material is preferably 30 hours or less, more preferably 20 hours or less, even more preferably 15 hours or less, and particularly preferably 10 hours or less.

[0114] In addition, the grinding time of the yttria raw material is preferably 1 hour or more, more preferably 2 hours or more, and even more preferably 5 hours or more. Through such grinding treatment, the stabilizer powder is obtained to have at least one peak top in the range of particle size 0.05 to 0.40 μm and at least one peak top in the range of particle size 0.5 μm or more in the volume-based particle size distribution.

[0115] The grinding time can be appropriately adjusted so that yttria powder having the desired peak top described above is obtained.

[0116] By including the above-mentioned stabilizer powder in the zirconia-containing composition, the above-mentioned desired ratio of medium particles, large particles, and small particles is obtained in the zirconia sintered body after firing.

[0117] In addition, zirconia powder is manufactured by grinding zirconia raw materials separately from yttria raw materials.

[0118] The reason for grinding the yttria raw material and the zirconia raw material separately is that, in order to produce yttria powder with a desired peak top, it is preferable to differentiate the grinding conditions for the yttria and zirconia raw materials, such as using materials with different particle sizes or different grinding times.

[0119] The average particle size (average primary particle size) of the yttria raw material for obtaining yttria powder having a desired particle size distribution after grinding is preferably 1.0 μm or more, and more preferably 2.0 μm or more, in that the ratio of the desired medium, large, and small particles is obtained in the zirconia sintered body after firing by using a raw material powder mixed with yttria powder and zirconia powder. In addition, the average particle size of the yttria raw material is preferably less than 10 μm, and more preferably 8 μm or less, in that the ratio of the desired medium, large, and small particles is obtained in the zirconia sintered body after firing by using a raw material powder mixed with yttria powder and zirconia powder. The above average particle size can be measured on a volume basis by, for example, using a laser diffraction / scattering particle size distribution measuring device (product name "Partica LA-950") manufactured by Horiba Corporation, irradiating a slurry diluted with water with ultrasound for 30 minutes, and then applying ultrasound.

[0120] In addition, the average particle size (average primary particle size) of the raw material for obtaining zirconia powder after grinding is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more, in that using a raw material powder mixed with yttria powder and zirconia powder allows the ratio of the desired medium, large, and small particles to be obtained in the zirconia sintered body after firing. In addition, the average particle size of the raw material for zirconia is preferably less than 1 μm, more preferably 0.6 μm or less, and even more preferably 0.4 μm or less. The average particle size of the raw material for zirconia can be measured in the same way as the average particle size of the raw material for yttria.

[0121] As for the raw material for zirconia, it is desirable to include monoclinic elements, as they maintain strength and exhibit excellent translucency even when sintered in a short time. The proportion of monoclinic elements in the raw material for zirconia f m It is preferable that the total amount of monoclinic, tetragonal, and cubic crystals be 60% or more, and it is more preferable that the amount be 70% or more, which is more preferable that the transparency is superior even when fired in a short time, 80% or more, even more preferable that the amount be 90% or more, and particularly preferable that the amount be 95% or more.

[0122] Proportion of monoclinic system f m It is calculated by the following formula (2).

[0123] f m = I m / ( I m + I t + I c ) × 100 (2)

[0124] (in the food, f m represents the proportion (%) of the monoclinic system of the zirconia raw material, and in XRD measurement, I mrepresents the monoclinic peak intensity near 2θ = 28°, and I t represents the peak intensity of the tetragonal system near 2θ = 30.2°, and I c represents the cubic peak intensity near 2θ = 30.1°.)

[0125] The proportion of monoclinic elements in the zirconia raw material f m With this above ratio, the same monoclinic ratio f is obtained in the zirconia molded body and zirconia plastic body. m This is obtained.

[0126] The zirconia-containing composition of the present invention may contain additives other than zirconia and stabilizers, provided that it exhibits the effects of the present invention. Examples of such additives include coloring agents (including pigments, complex pigments, and fluorescent agents), binders, dispersants, defoaming agents, alumina (Al2O3), titanium oxide (TiO2), silica (SiO2), etc. One type of additive may be used alone, or two or more types may be used in combination.

[0127] The zirconia-containing composition of the present invention may be in a dried state, or in a state containing a liquid or contained in a liquid. For example, the zirconia-containing composition may take the form of a powder, a paste, a slurry, etc.

[0128] The present invention includes embodiments in which the above configurations are combined in various ways within the scope of the technical concept of the present invention, as long as they exhibit the effects of the present invention.

[0129] Examples

[0130] Next, the present invention will be described more specifically with reference to examples, but the present invention is not limited in any way by these examples, and many modifications are possible by those skilled in the art within the scope of the technical concept of the present invention.

[0131] [raw material]

[0132] As raw materials for zirconia and yttria, the following raw materials 1, 2, and 3 were used.

[0133] Raw material 1 used zirconia powder in which the monoclinic type was 99% or more, the average primary particle size was 100 nm, and the average particle size was 11 μm.

[0134] Raw material 2 used yttria powder with an average particle size of about 3200 nm.

[0135] Raw material 3 used zirconia powder "Zpex Smile (registered trademark)" manufactured by Tosoh Corporation.

[0136] [Examples 1 to 14]

[0137] <Preparation of Zirconia Slurry>

[0138] The raw material for zirconia (raw material 1) was added to water. This and zirconia beads were placed in a rotary container, and the raw material was ground (disintegrated) by ball milling so that the particles contained in the slurry had a desired average particle size (approx. 100 nm). The particle size was measured using a laser diffraction / scattering particle size distribution measuring device (product name "Partica LA-950") manufactured by Horiba, Ltd., by ultrasonically irradiating the water-diluted slurry for 30 minutes, and then measuring the volume while applying ultrasound. The desired zirconia slurry was obtained after a ball milling time of approximately 20 hours.

[0139] <Manufacture of Yttria Slurry>

[0140] Next, the yttria raw material (raw material 2) was added to water. This and zirconia beads were placed in a rotary container, and the raw material was ground by ball milling so that the particles contained in the slurry had a desired particle size (the ratio of peak top frequency in the range of 0.05 to 0.40 μm (A) to peak top frequency in the range of 0.50 μm or more (B) was 50:50 to 79:21). The particle size was measured on a volume basis while applying ultrasound, using a laser diffraction / scattering particle size distribution measuring device manufactured by Horiba Corporation (product name "Partica LA-950"). The slurry diluted with water was ultrasonically irradiated for 30 minutes, and then measured. The desired yttria slurry was obtained after a ball milling time of approximately 6 to 20 hours.

[0141] Next, the obtained zirconia slurry and the obtained yttria slurry were mixed, an organic binder was added, and the mixture was stirred with a rotary blade. The slurry after stirring was dried and granulated using a spray dryer to obtain a powder. The average particle size of the powder was 40 μm. This powder was poured into a columnar mold and uniaxially pressed at a pressure of 33 MPa, followed by additional CIP treatment at 170 MPa to obtain a molded body. The molded body was placed in an electric furnace, heated from room temperature at a rate of 10 °C / min, held at 500 °C for 2 hours to degrease the organic components, held at 1000 °C for 2 hours, and slow-cooled at -0.4 °C / min to obtain a zirconia plastic. The obtained zirconia plastic was heated at a rate of 10 ℃ / min to the firing temperature (maximum firing temperature) listed in Table 1 and held for the time listed in Table 1 to obtain a zirconia sintered body.

[0142] [Comparative Examples 1 to 3]

[0143] Zirconia raw material (raw material 1) and yttria raw material (raw material 2) were added to water. These and zirconia beads were placed in a rotary container and ground with a ball mill. At this time, by adjusting the time of ball milling, large particle size powder with a large average particle size (average particle size 0.4 μm) and small particle size powder with a small average particle size (0.08 μm) were produced. The particle size was measured on a volume basis while applying ultrasound, using a laser diffraction / scattering particle size distribution measuring device (product name "Partica LA-950") manufactured by Horiba Corporation, after ultrasonically irradiating a slurry diluted with water for 30 minutes.

[0144] Next, large-sized powder and small-sized powder were mixed. The mixing ratio of the large-sized powder to the small-sized powder was set to 1:2 to 2:1. Titanium oxide, aluminum oxide, and an organic binder were added to the obtained slurry, and the mixture was stirred with a rotary blade. The slurry after stirring was dried and granulated using a spray dryer to obtain powder. The average particle size of the powder was 40 μm. This powder was poured into a columnar mold and subjected to uniaxial pressure pressing at a pressure of 33 MPa, followed by additional CIP treatment at 170 MPa to obtain a molded body. The molded body was placed in an electric furnace, heated from room temperature at a rate of 10 °C / min, held at 500 °C for 2 hours to degrease the organic components, held at 1000 °C for 2 hours, and slow-cooled at -0.4 °C / min to obtain a zirconia plastic. The obtained zirconia plastic was heated at a rate of 10 ℃ / min to the firing temperature (maximum firing temperature) listed in Table 1 and held for the time listed in Table 1 to obtain a zirconia sintered body.

[0145] [Comparative Example 4]

[0146] Zirconia powder "Zpex Smile" (registered trademark) manufactured by Tosoh Co., Ltd. (raw material 3) was poured into a columnar mold and uniaxially pressed at a pressure of 33 MPa, and then further subjected to CIP treatment at 170 MPa to obtain a molded body. The molded body was placed in an electric furnace, heated from room temperature at a rate of 10 °C / min, held at 500 °C for 2 hours to degrease organic components, held at 1000 °C for 2 hours, and then slowly cooled at -0.4 °C / min to obtain a zirconia plastic. The obtained zirconia plastic was heated at a rate of 10 °C / min to the firing temperature (maximum firing temperature) listed in Table 1 and held for the time listed in Table 1 to obtain a zirconia sintered body.

[0147] For the zirconia sintered bodies prepared in each example and comparative example, each characteristic was measured by the following method.

[0148] <Method for Measuring the Ratio of Particle Sizes>

[0149] In each example or comparative example, a surface image (SEM image) of the sintered body obtained was obtained using a scanning electron microscope (product name "VE-9800", manufactured by Keyence Co., Ltd.).

[0150] After marking the grain boundaries of each crystal grain on the obtained image, the crystal grain size was calculated through image analysis.

[0151] Image analysis software (product name "Image-Pro Plus ver.7.0.1", manufactured by Hakuto Co., Ltd.) was used to measure the particle size, the introduced SEM image was binarized, the brightness range was adjusted so that the grain boundaries became clear, and the particles were recognized from the field of view (area).

[0152] The particle diameter obtained with Image-Pro Plus is the diameter passing through the center of gravity of the particle, and the particle diameter is the average of the measured values ​​(180) obtained by measuring the length of the line segment connecting the outlines passing through the center of gravity obtained from the outline of the particle at 2-degree intervals centered on the center of gravity.

[0153] Particles that are not caught in the image edge were subject to measurement. "Particles not caught in the image edge" refers to particles excluding particles whose outlines do not fully fit within the frame of the SEM photograph (particles whose outlines are interrupted in the middle at the top, bottom, left, and right boundary lines).

[0154] The crystal grain size of all particles not caught in the image layer was selected as an option to exclude all particles on the boundary line in Image-Pro Plus.

[0155] For one sample of each example and comparative example, the particle diameter of each particle in three fields of view was obtained.

[0156] Figure 2 shows an SEM image of the zirconia sintered body of Example 5. Figure 3 shows an SEM image of the zirconia sintered body of Comparative Example 1, and Figure 4 shows an SEM image of the zirconia sintered body of Comparative Example 4.

[0157] For each example and comparative example, the particle size data of each particle obtained was classified into three classes: less than 0.45 μm, 0.45 μm or more and less than 1.0 μm, and 1.0 μm or more, and the ratio of the number of data for each particle size range was calculated when the total number of data was set to 100%.

[0158] <Method for Measuring the Transmittance of a Sintered Body>

[0159] The obtained zirconia sintered body was polished into a flat plate sample with a thickness of 1.20 mm. For the said sample, using a spectrophotometer manufactured by Olympus Corporation (product name "Crystal Eye"), in measurement mode: 7-band LED light source, the lightness (L) when measuring chromaticity against a white background W * ) and the lightness (L) when chromaticity is measured on a black background using the same sample, the same measuring device, measurement mode, and light source. B * ) measures, and the difference between the two (ΔL * = (L W * ) - (L B * )) transmittance (ΔL * (WB)) was set as (n = 3).

[0160] The average value of the measurements is shown in Table 1. Transmittance ΔL * (WB) was evaluated as “○” for 15 or higher, “△” for 13 or higher but less than 15, and “×” for less than 13. From the perspective of manufacturing prostheses having a color tone close to natural teeth (especially incisors and canines), ΔL * It is preferable that (WB) be 13 or higher, more preferable that it be 14 or higher, and even more preferable that it be 15 or higher.

[0161] <Method for Measuring Biaxial Bending Strength of Sintered Body>

[0162] A sample with a diameter of 15 mm and a thickness of 1.2 mm was obtained from the obtained zirconia sintered body. The biaxial bending strength of the obtained sintered body was measured using a universal precision testing machine Autograph (product name “AG-I 100kN”) manufactured by Shimadzu Corporation in accordance with JIS T 6526:2012 at a crosshead speed of 1.0 mm / min (n = 5). The biaxial bending strength was evaluated as “○” for 550 MPa or more and “×” for less than 550 MPa.

[0163] <Method for Measuring Crystalline Boundary Ratios of Tetragonal and Cubic Systems>

[0164] The surface of the zirconia sintered body was mirror-finished, X-ray diffraction (XRD) measurements were performed, and the result was obtained using the following formula.

[0165] f t / (t+c) = 100 × I t / ( I t + I c ) (1)

[0166] Here, f t / (t+c) represents the ratio of tetragonal to (tetragonal + cubic) in the zirconia sintered body, and I t represents the height of the peak near 2θ = 30.2° (peak based on the tetragonal system), and I c represents the height of the peak (peak based on the cubic system) near 2θ = 30.1°.

[0167]

[0168] From the above results, it was confirmed that the zirconia sintered body of the present invention can achieve both high transparency and high strength, which can be preferably used in anterior teeth and canines (particularly central incisors and lateral central incisors). In addition, it was confirmed that high transparency and strength can be achieved even with short-term firing, as the transparency is excellent despite being fired in a short time, and the strength is higher compared to conventional firing (firing maintained at the maximum firing temperature for 120 minutes).

[0169] In contrast, in Comparative Examples 1 to 3, the same ratio of heavy particles as in the Example was not obtained. Consequently, in Comparative Examples 1 to 3, the same ratio of heavy particles as in the Example was not obtained, and high transparency was not obtained. Furthermore, in Comparative Example 4 corresponding to Patent Document 2, since yttria raw material was not distinguished as a raw material, yttria was dissolved in zirconia, and the same ratio of heavy particles as in the Example was not obtained, and high strength was not obtained.

[0170] Comparative Examples 1 to 3 above correspond to Examples 24, 26, and 1 of Patent Document 1 (International Publication No. 2014 / 142080), respectively, as shown in Table 2 below.

[0171]

[0172] Industrial applicability

[0173] The zirconia sintered body of the present invention can be preferably used for dental purposes. In particular, the zirconia sintered body of the present invention is useful as a dental prosthesis for anterior teeth and canines (particularly central incisors and lateral central incisors).

Claims

Claim 1 A zirconia sintered body comprising zirconia and a stabilizer capable of suppressing the phase transition of zirconia, wherein the crystal grains of the zirconia sintered body, in a particle size distribution based on the number of particles, contain particles with a particle size of 0.45 μm or more and less than 1 μm in a ratio of 20 to 50%, particles with a particle size of less than 0.45 μm in a ratio of 20 to 70%, and particles with a particle size of 1 μm or more in a ratio of 6 to 35%, wherein the particle size is a diameter passing through the center of gravity of the particles. Claim 2 A zirconia sintered body according to claim 1, wherein the crystal grains of the zirconia sintered body contain, in a particle size distribution based on the number of particles, particles with a particle size of less than 0.45 μm in a ratio of 22.7 to 67.1%. Claim 3 A zirconia sintered body according to claim 1, wherein the crystal particles of the zirconia sintered body contain particles having a particle diameter of 1 μm or more in a ratio of 7.9 to 31.7% in a particle diameter distribution based on the number. Claim 4 A zirconia sintered body according to claim 1, wherein in the crystal system of the zirconia above, the ratio of the tetragonal system to the sum of the tetragonal system and the cubic system, calculated by the following formula (1), is 0 to 70%. t / (t+c) = 100 × I t / ( I t + I c ) (1) (among the formula, f t / (t+c) represents the ratio of tetragonal to (tetragonal + cubic) in the zirconia sintered body measured by X-ray diffraction, and I t represents the height of the peak near 2θ = 30.2° (peak based on the tetragonal system), and I c represents the height of the peak near 2θ = 30.1° (the peak based on the cubic system). Claim 5 A zirconia sintered body according to claim 4, wherein the ratio of the tetragonal system to the sum of the tetragonal and cubic systems is 40 to 65 percent. Claim 6 A zirconia sintered body according to claim 1, wherein the biaxial bending strength measured in accordance with JIS T 6526:2012 is 550 MPa or higher. Claim 7 In claim 1, the stabilizer is yttria, zirconia sintered body. Claim 8 A zirconia sintered body according to claim 7, wherein the yttria content is 3.0 to 7.5 mol% with respect to the total mol of zirconia and yttria. Claim 9 A method for manufacturing a zirconia sintered body comprising zirconia and a stabilizer capable of suppressing the phase transition of zirconia, wherein a raw material powder comprising zirconia powder and a stabilizer powder capable of suppressing the phase transition of zirconia is used, and wherein the stabilizer powder comprises a powder having at least one peak top in a range of particle size of 0.05 to 0.40 μm in a volume-based particle size distribution and at least one peak top in a range of particle size of 0.5 μm or more. Claim 10 A method for manufacturing a zirconia sintered body according to claim 9, wherein in the volume-based particle size distribution of the stabilizer powder, the ratio (A) : (B) of the frequency of peak tops in the range of particle size 0.05 to 0.40 μm and the frequency of peak tops in the range of particle size 0.5 μm or more is 40 : 60 to 85 :

15. Claim 11 In claim 9, the above-mentioned stabilizer is yttria, a method for manufacturing a zirconia sintered body. Claim 12 A method for manufacturing a zirconia sintered body according to claim 11, wherein the yttria content is 3.0 to 7.5 mol% with respect to the total mol of zirconia and yttria. Claim 13 A method for manufacturing a zirconia sintered body according to claim 9, wherein the above raw material powder is molded to produce a zirconia molded body. Claim 14 A method for manufacturing a zirconia sintered body according to claim 13, wherein the zirconia molded body is sintered to produce a zirconia plastic. Claim 15 A method for manufacturing a zirconia sintered body according to claim 14, wherein the manufactured zirconia plastic is further sintered. Claim 16 A method for manufacturing a zirconia sintered body according to claim 13, wherein the zirconia molded body is fired to produce a zirconia sintered body. Claim 17 A method for manufacturing a zirconia plastic comprising zirconia and a stabilizer capable of suppressing the phase transition of zirconia, wherein a raw material powder comprising zirconia powder and a stabilizer powder capable of suppressing the phase transition of zirconia is used, and wherein the stabilizer powder comprises a powder having at least one peak top in a range of particle size of 0.05 to 0.40 μm and at least one peak top in a range of particle size of 0.5 μm or more in a volume-based particle size distribution. Claim 18 A method for manufacturing a zirconia plastic according to claim 17, wherein the raw material powder is molded to produce a zirconia molded body. Claim 19 In claim 18, a method for manufacturing a zirconia plastic, wherein the zirconia molded body is plasticized. Claim 20 A method for preparing a zirconia-containing composition comprising zirconia and a stabilizer capable of suppressing the phase transition of zirconia, wherein the raw material of the zirconia is ground to produce zirconia powder, the raw material of the stabilizer is ground to produce stabilizer powder, and the zirconia powder and the stabilizer powder are mixed to produce a zirconia composition which is a raw material powder, wherein the stabilizer powder comprises a powder having at least one peak top in a range of particle size of 0.05 to 0.40 μm and at least one peak top in a range of particle size of 0.5 μm or more in a volume-based particle size distribution. Claim 21 A method for manufacturing a zirconia-containing composition according to claim 20, wherein the grinding time of the raw material of the stabilizer is 30 hours or less. Claim 22 A method for preparing a zirconia-containing composition according to claim 20 or 21, wherein the grinding time of the raw material of the zirconia is 20 hours or more. Claim 23 A method for preparing a zirconia-containing composition, wherein the stabilizer in claim 20 or 21 is yttria.

Citation Information

Patent Citations

  • Light-transmitting sintered zirconia compact, method for producing the same, and use thereof

    JP2009269812A

  • Zirconia material and method

    JP2010514665A

  • Sintered body of zirconia and method for manufacturing the same

    JP2011073907A

  • Light-transmitting zirconia sintered compact, zirconia powder and application thereof

    JP2015143178A

  • Method for producing powder containing zirconia particles

    KR1020200035279A